Transmembrane activator and calcium-modulating cyclophilin ligand interactor mutations in common variable immunodeficiency: Clinical and immunologic outcomes in heterozygotes - Zhang, Li; Radigan, Lin; Salzer, Ulrich; Behrens, Timothy W.; Grimbacher, Bodo; Diaz, George; Bussel, James; Cunningham-Rundles, Charlotte (Journal of allergy and clinical immunology, 2007)
Mutations in the gene coding for transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI) have been identified in common variable immunodeficiency (CVID). Mutations coincided with immunodeficiency in families, suggesting dominant inheritance. Because most subjects with CVID have no immunodeficient family members and heterozygous mutations predominate, the role of TACI mutations in sporadic CVID is unclear. TACI was sequenced from the genomic DNA of 176 subjects with CVID and family members. B cells of subjects with or without mutations were examined for binding to the ligand, a proliferation inducing ligand (APRIL), and for proliferation and immunoglobulin production after ligand stimulation. Data analysis was performed to assess the clinical relevance of TACI mutations. Heterozygous TACI mutations were found in 13 subjects (7.3%). Six with mutations (46%) had episodes of autoimmune thrombocytopenia, in contrast with 12% of 163 subjects without mutations; splenomegaly and splenectomy were significantly increased ( P = .012; P = .001.) B cells of some had impaired binding of APRIL and on culture with this ligand were defective in proliferation and immunoglobulin production; however, this was not different from B cells of subjects without mutations. Eight first-degree relatives from 5 families had the same mutations but were not immune-deficient, and their B cells produced normal amounts of IgG and IgA after APRIL stimulation. Mutations in TACI significantly predispose to autoimmunity and lymphoid hyperplasia in CVID, but additional genetic or environmental factors are required to induce immune deficiency. Additional causes of this common immune deficiency syndrome remain to be determined.